Metabolic adaptations to short-term high-intensity interval training: A little pain for a lot of gain? - Gibala, M. J.; McGee, S. L. (Exercise and Sport Sciences Reviews, 2008)
High-intensity interval training (HIT) is a potent time-efficient strategy to induce numerous metabolic adaptations usually associated with traditional endurance training. As little as six sessions of HIT over 2 wk or a total of only approximately 15 min of very intense exercise (~600 kJ), can increase skeletal muscle oxidative capacity and endurance performance and alter metabolic control during aerobic-based exercise.